Brief Research Report: Veterinary Student Perspective on COVID-19 and Veterinary Medicine - Limper, Candice B.; Hinckley-Boltax, Ariana L.; Cazer, Casey L. (Frontiers in Veterinary Science, 2021)
COVID-19 has had significant effects on the field of veterinary medicine. Adaptation to pandemic-related and post-pandemic challenges requires engagement from all levels of the professional pipeline, including veterinary college students. Insights gained from this group may inform curriculum design, help the veterinary profession innovate, maximize opportunities for positive change, and avoid negative outcomes. The current study aimed to understand the potential impacts of the COVID-19 pandemic on veterinary medicine, as foreseen by second-year veterinary students in an online discussion during a public health course in the spring of 2020. Twenty-one percent of the 113 students agreed to participate in this qualitative research study. We used an inductive coding process and distilled the student responses into descriptive themes to capture diverse perspectives and understand possible post-pandemic pathways for the veterinary profession. Four themes emerged from the student discussion posts, describing how veterinarians might be affected by the COVID-19 pandemic: 1) economic and social impacts, 2) adapting to challenges, 3) collaborations to improve public health, and 4) disparities and diversity. These themes are a starting point for discussion and innovation as veterinarians plan for the post-pandemic world; further investigation will provide additional guidance for veterinary leaders.